Determinan Pendapatan Pedagang Kaki Lima di Kecamatan Samarinda Utara - novia Ranisa; Theresia militina; Andriawan kustiawan (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
This study is entitled "Determinants of Street Vendor Income in North Samarinda District". The purpose of this study was to analyze the effect of capital, working hours, business hours, number of workers, and costs on the income of street vendors in the North Samarinda District and to determine the amount of income to MSEs. This study uses primary data through interviews and questionnaires on 50 respondents taken through accidental sampling. The analytical method multiple linear regression. The results costs had a negative and real effect on the income of street vendors in the North Samarinda District, capital had a positive and real effect on the income of the street vendors in the North Samarinda District while working hours, length of business, number of workers did not significantly affect the income of the street vendors in the North Samarinda District. North Samarinda. Based on research, it is known that the income of street vendors in North Samarinda District has exceeded the City of Samarinda's MSE.